Performance Analysis Based on the Balanced Scorecard Approach (Case Study at the Maya Sanur Resort and Spa Hotel) - Ni Luh Putu Wiagustini; Luh Komang Candra Dewi; Ni Putu Vicky Yudiari (Jurnal Mirai Management, 2026)
This study aims to analyze the performance of Maya Sanur Resort & Spa using the Balanced Scorecard approach, which encompasses the financial, customer, internal business process, and learning and growth perspectives. The research employed a descriptive quantitative approach, with data collected through questionnaires distributed to customers and employees, as well as secondary data obtained from the company. Data analysis was conducted using a Likert scale and descriptive statistical techniques. The results indicate that the overall performance of the hotel falls within the good category. The customer perspective achieved a score of 3.82, indicating a high level of customer satisfaction and loyalty. The internal business process perspective obtained a score of 3.57, reflecting fairly effective operational performance. The learning and growth perspective scored 3.70, demonstrating favorable conditions in human resource development. Meanwhile, the financial perspective, measured using Return on Assets (ROA), was categorized as very good, with a value exceeding 10 percent. Overall, the hotel's performance index was classified as good and approaching the very good category